DNA–gadolinium–gold nanoparticles for in vivo T1 MR imaging of transplanted human neural stem cells. (January 2016) - Nicholls, Francesca J.; Rotz, Matthew W.; Ghuman, Harmanvir; MacRenaris, Keith W.; Meade, Thomas J.; Modo, Michel
Abstract: The unambiguous imaging of transplanted cells remains a major challenge to understand their biological function and therapeutic efficacy. In vivo imaging of implanted cells is reliant on tagging these to differentiate them from host tissue, such as the brain. We here characterize a gold nanoparticle conjugate that is functionalized with modified deoxythymidine oligonucleotides bearing Gd(III) chelates and a red fluorescent Cy3 moiety to visualize in vivo transplanted human neural stem cells. This DNA-Gd@Au nanoparticle (DNA-Gd@AuNP) exhibits an improved T1 relaxivity and excellent cell uptake. No significant effects of cell uptake have been found on essential cell functions. Although T1 relaxivity is attenuated within cells, it is sufficiently preserved to afford the in vivo detection of transplanted cells using an optimized voxel size. In vivo MR images were corroborated by a post-mortem histological verification of DNA-Gd@AuNPs in transplanted cells. With 70% of cells being correctly identified using the DNA-Gd-AuNPs indicates an overall reliable detection. Less than 1% of cells were false positive for DNA-Gd@AuNPs, but a significant number of 30% false negatives reveals a dramatic underestimation of transplanted cells using this approach. DNA-Gd@AuNPs therefore offer new opportunities to visualize transplanted cells unequivocally using T1 contrast and use cellular MRI as a tool to derive biologically relevant information that allows us to understand how the survival and location of implanted cells determines therapeutic efficacy. Graphical abstract: